Clostridium piliforme and canine distemper virus coinfection in 2 domestic dog littermates and a gray fox kit. (September 2022) - Jacobson, Sarah A.; Ferro, Pamela J.; Navarro, Mauricio A.; Uzal, Francisco A.; Edwards, Erin E.
Concurrent Clostridium piliforme and canine distemper virus (CDV) infection was diagnosed in 2 canine littermates and 1 gray fox kit from Texas, USA. In all 3 animals, intracytoplasmic, filamentous bacteria, consistent with C. piliforme, were present along the margins of foci of hepatic necrosis. Additional histologic findings included intracytoplasmic and intranuclear inclusion bodies in bile duct and bronchial epithelial cells of the fox kit, and mild intestinal necrosis in 1 puppy. PCR assays confirmed the presence of C. piliforme in all 3 animals, CDV in both puppies, and canine parvovirus in 1 puppy. Fluorescent antibody testing confirmed the presence of CDV in the fox kit. Concurrent canine distemper and Tyzzer disease in canine littermates and the gray fox has not been reported previously, to our knowledge.